2010
DOI: 10.1007/978-3-642-17517-6_27
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Stream Programs: Characterizing Type 2 Polynomial Time Complexity

Abstract: Abstract. We study polynomial time complexity of type 2 functionals. For that purpose, we introduce a first order functional stream language. We give criteria, named well-founded, on such programs relying on second order interpretation that characterize two variants of type 2 polynomial complexity including the Basic Feasible Functions (BFF). These characterizations provide a new insight on the complexity of stream programs. Finally, we adapt these results to functions over the reals, a particular case of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Using an approach similar to the one presented in this paper, Férée et al [16] show that interpretations can be used on stream programs also to characterize type 2 polynomial time functions. In particular, they extend interpretations in order to use second order polynomials to characterize the set of functions computable in polynomial time by Oracle Turing Machines and by their unitary version.…”
Section: Related Workmentioning
confidence: 99%
“…Using an approach similar to the one presented in this paper, Férée et al [16] show that interpretations can be used on stream programs also to characterize type 2 polynomial time functions. In particular, they extend interpretations in order to use second order polynomials to characterize the set of functions computable in polynomial time by Oracle Turing Machines and by their unitary version.…”
Section: Related Workmentioning
confidence: 99%
“…Using an approach based on quasi-interpretation, in [12,13] we have studied space upper bounds properties and input-output properties of programs working on streams. Using a similar approach Férée et al [10] showed that interpretations can be used on stream programs also to characterize type 2 polynomial time functions by providing a characterization of the class of the Basic Feasible Functionals of Cook and Urquhart [9].…”
Section: Related Workmentioning
confidence: 99%
“…Using an approach based on quasi-interpretation, in [12,13] we have studied space upper bounds properties and input-output properties of programs working on streams. Using a similar approach Férée et al [10] showed that interpretations can be used on stream programs also to characterize type 2 polynomial time functions by providing a characterization of the class of the Basic Feasible Functionals of Cook and Urquhart [9].…”
Section: Related Workmentioning
confidence: 99%